Continuous Cover Forestry and Cost of Carbon Abatement on Mineral Soils and Peatlands - Ahtikoski, Anssi; Rämö, Janne; Juutinen, Artti; Shanin, Vladimir; Mäkipää, Raisa (Frontiers in Environmental Science, 2022)
Continuous cover forestry (CCF) has proven to financially outperform rotation forestry (RF) with low or even moderate social price of carbon in mineral soils. However, to date there are no studies to compare financial performance of joint production (timber and carbon sequestration) between mineral soils and peatlands when CCF is applied. A vast variety of harvest intervals and intensity (expressed as post-harvest basal area) for a mature spruce-dominated (Picea abies (L.) Karst.) stand on both mineral and peat soils was simulated with process-based ecosystem model, EFIMOD. In addition, four levels of carbon price (0, 25, 50 and 75€/tCO2) were applied in assessing the profitability of joint production (timber and carbon sequestration) associated with CCF. Mineral soil turned out to be superior to peatland in cost-efficiency of carbon sequestration. For instance, the cost of additional ton of CO2 was only €2/tCO2 with a carbon price of €25/tCO2 for a private forest owner (through carbon trading), while on peatland it fluctuated between €30 and €39.5/tCO2, depending on the carbon price applied for a private forest owner (€25-€75/tCO2). In general, mineral soil was more sensitive to harvest interval and intensity than peatland, with respect to cost-efficiency in climate change mitigation.